Assessing female labour force participation rate in the construction industry. - Hudu, Issahaku (2015)
A thesis Submitted to the Department of Managerial Sciences, Kwame Nkrumah University of Science and Technology (KNUST), in partial fulfillment of the requirement for the degree of MASTER OF BUSINESS ADMINISTRATION (HUMAN RESOURCE MANAGEMENT-OPTION). 2014